Dorylomorpha Aczél, 1939 (Diptera: Pipunculidae) of South America, with description of two new subgenera and 11 new species - Ramos-Pastrana, Yardany; Amat, Eduardo; Rafael, José Albertino (Zootaxa, 2026)
Dorylomorpha Aczél, 1939 is a cosmopolitan genus (except in the afrotropics), with three species from South America, one each in Brazil, Colombia, and Peru. Two new subgenera and 11 new species are described here from Brazil, Colombia, and Ecuador, namely: Dorylomorpha (Monticola) subgen. nov., including the following species: Dorylomorpha (Monticola) brasiliensis sp. nov., D. (M.) boyacensis sp. nov., D. (M.) chingaensis sp. nov., D. (M.) ecuadorensis sp. nov., D. (M.) flaviabdominalis sp. nov., D. (M.) huilensis sp. nov., D. (M.) laeta (Becker, 1900) (here redescribed), D. (M.) narignensis sp. nov., D. (M.) risaraldensis sp. nov. (type species of the subgenus Monticola) and D. (M.) santamartensis sp. nov. Dorylomorpha (Paramuna) subgen. nov., including the following species: D. (Paramuna) flavipes sp. nov. and D. (Paramuna) nigripes sp. nov. (type species of the subgenus Paramuna). In addition, species of the subgenus Dorylomorpha (Pipunculina) Albrecht 1990, including D. (Pipunculina) lenkoi Hardy, 1965 and D. (Pipunculina) reveloi Hardy, 1963 are redescribed. Illustrations, dichotomic keys, and distribution maps to Neotropical subgenera and species of all subgenera are provided.